Answer:
- 14x - 15
Explanation:
(4x + 3) (2x - 5)
you multiply everything in the second parentheses by the first number in the first parentheses
write those numbers down
then multiply the number in the second parentheses again by the second factor in the first parentheses
(4x) (2x - 5)
4x · 2x = 8x²
8x²
4x · -5 = -20x
8x² - 20x
that's the first part of the equation
then, moving on
(3) (2x - 5)
3 · 2x = 6x
6x
3 · -5 = -15
6x - 15
then, put them together and you get
8x² - 20x + 6x - 15
add up all the like terms, in this case, the x ones
-20x + 6x = -14x
then, your answer would be:
8x² - 14x - 15